Shear Bond Strength of Lithium Disilicate Bonded with Various Surface-Treated Titanium - Laongdao Amornwichitwech; Mali Palanuwech (Hindawi Limited, 2022)
Purpose. Retention is one of the most important factors for fixed dental prostheses, especially in implant dentistry. Accordingly, the goal of this study was to evaluate the level of shear bond strength between titanium (Ti) subjected to different surface treatments and lithium disilicate glass-ceramics. Materials and Methods. In this work, 90 titanium alloy specimens were divided into six groups as follows: the control group (CT), 50 μm alumina airborne-particle abrasion group (SB), silica-coated group (CJ), anodization group (AN), anodization followed by alumina 50 μm airborne-particle abrasion group (ANSB), and anodization followed by silica coating group (ANCJ). Titanium specimens were bonded to lithium disilicate specimens with resin cement (Multilink N). The specimens were restored in water at 37°C for 24 h, and then, shear bond strength (SBS) tests were performed using a universal testing machine (Shimadzu, Japan). The SBS values were statistically analyzed. The failure mode of the debonded titanium was classified after viewing the samples under a stereoscope. Results. The results demonstrated that the mean SBSs of CT and AN were significantly lower than those of the other groups (p<0.05). The SB group showed the highest SBS (29.47 ± 2.41 MPa); however, there was no significant difference between SB, ANSB, ANCJ, and CJ. The stereoscopic analysis demonstrated that the failure mode of AN was predominantly adhesive failure; whereas, the other groups showed cohesive and mixed failures. Conclusions. In this study, it was found that the surface treatment with 50 μm alumina airborne-particle abrasion, silica coating with Cojet™ sand, anodization followed by 50 μm alumina airborne-particle abrasion, and anodization followed by silica coating with Cojet™ sand improved the SBS between titanium and lithium disilicate luted with Multilink N resin cement.